Induced feelings of external influence during instructed imaginations in healthy subjects - Eckstein, Kathrin N.; Rosenbaum, David; Zehender, Nadine; Pleiss, Sonja; Platzbecker, Sharon; Martinelli, Anne; Herrmann, Matthias L.; Wildgruber, Dirk (Frontiers in Psychology, 2022)
Delusions of influence, such as thought insertion, are a hallmark in psychotic diseases. Nevertheless, attenuated forms can also appear in healthy individuals. Here we present a newly developed paradigm to induce and assess feelings of external influence during instructed imaginations in healthy individuals. In the current study, we asked 60 healthy individuals to visually imagine different objects. To induce feelings of external influence, we applied one of three different physical setups (low-amplitude transcranial direct current stimulation, eye contact or skin-to-skin hand touch), and informed the participants whether or not an external influence was attempted during the respective trial. The physical setup (setup vs. no setup, Z = -3.847, p < 0.001, r = 0.497) as well as the information given to the participants (confirmation vs. negation, Z = -5.218, p < 0.001, r = 0.674) alone were able to modulate the feeling of external influence in all three interventions. The impact of information (whether influence was attempted or not attempted) significantly excelled the impact of the physical setup on the ratings of experienced external influence (Z = -2.394, p = 0.016, r = 0.310). Moreover, the promptness of the answers correlated inversely with the estimated feeling of external influence (rS = 0.392, p = 0.002). Additional analyses addressed the influence of the emotional content of imagined objects and examined the intensity and emotional valence of the imaginations. Further supplemental analyses correlated external influence estimation of the participants with other psychopathological measures (trait markers for supernatural beliefs, proneness to hallucinations and delusions and attributional style). In conclusion, this study endorses a quantitative model of psychopathological characteristics, in this case feelings of external influence, that can be induced by external cues.